An Interrupted Time Series Analysis Measuring the Impact of Research and Education on Clinical Practice: Decreasing Allograft Use in Young Patients Using a Registry to Track Outcomes. (19th April 2023) - Maletis, Gregory B.; Prentice, Heather A.; Wyatt, Ronald W.B.; Paxton, Elizabeth W.; Funahashi, Tadashi T.
Abstract : Background: We sought to evaluate whether allograft utilization for primary anterior cruciate ligament reconstruction (ACLR) within our health-care system changed following the implementation of an allograft reduction intervention and whether revision rates within the health-care system changed following the initiation of the intervention. Methods: We conducted an interrupted time series study using data from Kaiser Permanente's ACL Reconstruction Registry. In our study, we identified 11, 808 patients who were ≤21 years of age and underwent primary ACLR from January 1, 2007, through December 31, 2017. The pre-intervention period (15 quarters) was January 1, 2007, through September 30, 2010, and the post-intervention period (29 quarters) was October 1, 2010, through December 31, 2017. Poisson regression was used to evaluate trends over time in 2-year revision rates according to the quarter in which the primary ACLR was performed. Results: Allograft utilization increased pre-intervention from 21.0% in 2007 Q1 to 24.8% in 2010 Q3. Utilization decreased post-intervention from 29.7% in 2010 Q4 to 2.4% in 2017 Q4. The quarterly 2-year revision rate increased from 3.0 to 7.4 revisions per 100 ACLRs pre-intervention and decreased to 4.1 revisions per 100 ACLRs by the end of the post-intervention period. Poisson regression found an increasing 2-year revision rate over time pre-intervention (rate ratio [RR], 1.03 [95% confidence interval (CI), 1.00 to 1.06] per quarter) and a decreasing rate over time post-intervention (RR, 0.96 [95% CI, 0.92 to 0.99]). Conclusions: In our health-care system, we saw a decrease in allograft utilization following the implementation of an allograft reduction program. During the same period, a decrease in the ACLR revision rate was observed. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.